KAJIAN INTENSITAS PENAUNGAN DAN PENJARANGAN BUAH TERHADAP HASIL TANAMAN ARBEI Fragariasp - Dwie Retna Suryaningsih (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2001)
This study was done in â€œMateria Medicaâ€?, Technical Implementation Unit East Java Health Service Bureau, Batu, East java, from May to December 1995. It has an altitude of approximately 750 m above sea level. This study has the objective of determining light intensity and fruit thinning which maximize strawberry yield of high quality. A three replicate two factors experiment, laid out in a completely randomized design with repeated measurements were. The first factor was shading intensity consisting of three levels: unshaded, shading intensity of 40% and 65%. The second factor was fruit thinning consisting of three levels: no fruit thinning applied, fruit thinning of 40% and 60%. The result indicated that: (1) maximum growth and yield of strawberry was attained at 40% incoming light, (2) removing 40% of fruits in a cluster increased weight of individual fruit, (3) shading which passed 40% of incoming light coupled with fruit thinning of 40% was the best combination, (4) shading increased vitamin C content of strawberry fruit, and (5) yield components might be predicted from tiller number, flower number per plant, and fruit weight average.